Animated Video Education of 3M Behavior to Improve Knowledge of DHF Prevention Among School-Age Children - Sulisnadewi, Ni Luh Kompyang; Sipahutar, Ida Erni; Wedri, Ni Made; Suardana, I Wayan (Jurnal Pengabmas Masyarakat Sehat, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a public health problem in tropical countries like Indonesia. School-age children are vulnerable due to limited awareness and hygiene behavior. The 3M behavior—draining, closing, and burying—is an effective preventive strategy. However, conventional health education is often less attractive to children. Animated video is a visual-audio medium proven to enhance children’s learning engagement.Objective: This community service aimed to improve children’s knowledge about DHF prevention through 3M behavior using animated video education.Method The activity was conducted at SD No. 1 Pesinggahan, Klungkung, involving 53 students from grades IV–VI. The program consisted of pre-test, animated video viewing, discussion, and post-test. The difference in knowledge before and after education was analyzed descriptively.Result: Before education, 60.4% of children had moderate knowledge, and 39.6% had good knowledge. After education, 94.3% showed good knowledge and only 5.7% remained moderate. Animated video education effectively improved children’s understanding of 3M behavior and DHF prevention.Conclusion: Animated video is an effective and attractive medium to increase school-age children’s knowledge about DHF prevention through 3M behavior. This program can be implemented sustainably through school-based health education.